PENGARUH GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT BRECXELLE BERKAH UNITI KOTA DEPOK - Ilham, Nurul (Yayasan Education and Social Center, 2025)
This study aims to analyze the extent to which leadership style and work environment influence employee performance at PT Brecxelle Benture Bento. The approach used is quantitative with an associative method. The sample was determined using a saturated sampling technique, resulting in a total of 96 respondents. The data analysis process includes validity testing, reliability testing, classical assumption tests, regression analysis, correlation, determination, and hypothesis testing. The findings of the study indicate that leadership style has a significant impact on employee performance with a contribution of 34.6%, where the hypothesis test result shows that the t-value is greater than the t-table (7.049 > 1.986). Likewise, the work environment also has a significant influence, with a coefficient of determination of 43.8% and a t-value of 8.566, which also exceeds the t-table. Simultaneously, leadership style and work environment affect employee performance with a regression equation of 11.129 + 0.264x1 + 0.465x2. The total coefficient of determination is 48.4%, while the remaining 51.6% is influenced by other unexamined factors. The F-test result also shows a significant simultaneous effect, with an F-value of 43.306 greater than the F-table value of 3.090.